A MULTI-DIMENSIONAL APPROACH IN DEVELOPING A FRAMEWORK FOR INTERNAL QUALITY ASSURANCE OF SECOND CYCLE ENGINEERING PROGRAMMES - M. A. Abdul Hakeem; V. Thanikachalam (European Scientific Journal, ESJ, 2014)
The rapid growth of engineering education requires the propermaintenance of academic quality in educational institutions in order towithstand competition in the global market. External accreditation andinternal quality assurance are two very important processes that are carriedout in order to maintain the quality of engineering education. Accreditation isa process designed to determine whether or not an educational programmehas met or exceeded the published standards of the accreditation agency,whereas the purpose of internal quality assurance is to develop a qualityculture within an institution, and to implement a strategy for the continuousenhancement of quality. Although several quality assurance standards andguidelines have been established and implemented worldwide throughvarious international, regional and national agencies; relevant literaturesearches show that there is no common agreement or criterion that can beused in the quality assurance of engineering education. In this article, theauthors elaborate on several important issues regarding the accreditation andquality assurance of engineering education. The authors define internalquality assurance of an engineering programme as: enabled by certain qualityenablers, a structured process of quality analysis (benchmarking,monitoring, evaluating, assessing, guaranteeing and improving the quality)of the design, resources, delivery and outcomes of the programme; resultingin defect avoidance, strategic alignment, continuous improvement, andstakeholder trust. A brief outline of a multi-dimensional framework forinternal quality assurance of engineering programmes is provided in thisarticle.